Impacto do cuidado na qualidade de vida e saúde mental do cuidador familiar de idoso dependente - Cunha, Maria Tereza de Souza Neves da (2014)
Population aging and dependence caused by longevity increase make evident the character of familiar caregiver, object of this study. Specifically in Brazil, there are health politics focused on elderly people, aiming on healthcare. Although, familiar caregiver, that supports the dependent elder, many times finds itself as fragile as the elder, does not receive the proper attention relating to their health. The objective of this study was valuating life and mental health quality of the familiar caregiver starting from their impacting in taking care of the elder focusing on caregiver stress, mental health and social aspects imbricated on this relationship. The sample has been composed by 40 familiar caregivers over eighteen years old and from both of the genres. As methods, we had Barthel Scale to evaluate the elder dependence degree, WHOQOL-bref; the Informal Caregiver Stress Evaluative Questionary (QASCI); Self-Reporting Questionnaire - 20 (SRQ-20) and Life Satisfaction Scale, besides semi-structured interview applied in 10 caregivers from the sample. Also, a social-demographic questionnaire has been applied for a better view of participants information. According to quantitative results, most of the caregivers are over the 40 years old (82,5%), are female (87,5%), married (47,5%), with medium (45%) or low (17,5% fundamental and 17,5% never frequented school) scholar degree, mostly unemployed (47,5%) and with familiar income between one or three minimum salaries. Mostly, the caregiver is a son or daughter from the elder (62,5%). The dependent elders majority was female (67,5%) between 64 and 98 years old. Generally, the biggest dependences are activities related to bathing, personal hygiene, climbing ladders, dressing, using toilet, feeding and controlling urine, in this order. Common mental disorders diagnostic suspicion has obtained a prevalence of 40% for general sample, pointing that 16 caregivers rated in morbid suggestive scale for Common Mental Disorders. About the caregiver stress, it was observed a dominance of medium and high stress (M=53,02; DP=20,39; varying between 16 and 88). Life satisfaction rate between caregivers 41,87 (DP=15,17; varying between 10 and 80), so, for mostly (77%), evaluation was negative. When evaluated General Life Quality, participants presented positive evaluation, with a rate of 56,6 (DP=20,9; varying between 19 and 78). Therefore, analyzing factors that compound life quality, it was verified an impact of care in this evaluation, once there was no positive evaluation, being the environmental and social factors most harmed, followed by psychological and physical ones. About care time, it was verified a significant diference (t(38)=-2,435; p=0,02), on psychological factor, indicating that initial care (less than 2 years) offers biggest psychological risk. Probably, longest the time, easier it becomes an accommodation or situational adaptation, decreasing psychological damages. It is hoped that with this study realization, knowledge about elderly familiar caregivers to be expanded, focusing on their mental health and life quality, as so as verifying how public health works on these people that take care and need to be cared health.